A two-injection prostaglandin F(2α) presynchronization treatment decreases pregnancy rates of cycling replacement beef heifers - Monn, Ruby E (Transl Anim Sci, 2018)
Improving artificial insemination (AI) pregnancy rates in replacement heifers improves the genetic advancement within a herd. Heifers that have completed at least three estrous cycles prior to breeding have greater pregnancy rates compared to acyclic females. Therefore, it was hypothesized that a presynchronization treatment program consisting of two injections of prostaglandin F(2α) (PGF(2α)) prior to the start of the CO-Synch + 5 d CIDR protocol would initiate earlier attainment of puberty and more estrous cycles prior to AI, thus increasing AI pregnancy rates. All heifers were managed the same at two locations over the course of 2 yr. Heifers were randomly assigned to receive either the two-injection PGF(2α) presynchronization treatment (PreSynch; n = 105) or no presynchronization (Control; n = 106) prior to the start of estrous synchronization. On the first day of the trial, reproductive tract scores (RTSs), pelvic areas, body condition scores, and weights were collected on all heifers. All heifers were synchronized with the CO-Synch + 5 d CIDR protocol and fixed-time artificially inseminated with semen from a bull of known fertility. Blood samples were collected three consecutive times at 7 d intervals starting 45 d prior to estrous synchronization to determine the onset of puberty via analyzing progesterone concentrations. Pregnancy status to AI was assessed using ultrasonography diagnosis at approximately 30 and 60 d post insemination. Data were analyzed using PROC MIXED of SAS and reported as least square mean. The PreSynch treatment decreased AI pregnancy rates (52.2% vs. 38.1 ± 6.3% for Control vs. PreSynch, respectively; P = 0.06) and did not result in earlier attainment of puberty in beef heifers (P > 0.05). The PreSynch treatment did not impact pregnancy rates in heifers with an RTS of 3 or 4 (P > 0.05). However, PreSynch heifers with an RTS of 5 had decreased pregnancy rates (68.3% vs. 46.9 ± 10.1% for Control vs. PreSynch, respectively; P < 0.05). Finally, PreSynch heifers with increased body condition of 6 had decreased pregnancy rates when compared to Control heifers (37.5% vs. 62.5 ± 11.6%, respectively; P < 0.05). On the basis of these data, implementation of heifer breeding soundness examination at least 3 wk prior to the start of the breeding season may be beneficial for selecting replacement females; however, presynchronization with prostaglandins immediately prior to estrous synchronization will negatively affect AI pregnancy rates in cycling pubertal heifers.